2022
DOI: 10.3389/fpubh.2022.804734
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Potentially Preventable Hospitalizations of High-Cost Patients in Rural China

Abstract: IntroductionHigh-cost patients are characterized by repeated hospitalizations, and inpatient cost accounts for a large proportion of their total health care spending. This study aimed to assess the occurrence and costs of potentially preventable hospitalizations and explore contributing factors among high-cost patients in rural China.MethodsWe examined a population-based sample of patients using the 2016 New Rural Cooperative Medical Scheme in Dangyang city, China. Eighteen thousand forty-three high-cost patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…[7][8][9] According to our previous study on the rural population, the occurrence of potentially preventable hospitalization (PPH) among highcost patients was sizable (22%), indicating that 22 preventable hospitalizations occurred per 100 high-cost persons. 10 Moreover, the preventable inpatient cost (PIC) of high-cost patients amounted to the majority (around 70%) of total preventable spending of overall patients as previous studies reported. 6,[10][11][12] Although high-cost patients only occupy a small proportion of the population, they are highly heterogeneous, which has substantial variations in demographics, functional status and disease burden.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[7][8][9] According to our previous study on the rural population, the occurrence of potentially preventable hospitalization (PPH) among highcost patients was sizable (22%), indicating that 22 preventable hospitalizations occurred per 100 high-cost persons. 10 Moreover, the preventable inpatient cost (PIC) of high-cost patients amounted to the majority (around 70%) of total preventable spending of overall patients as previous studies reported. 6,[10][11][12] Although high-cost patients only occupy a small proportion of the population, they are highly heterogeneous, which has substantial variations in demographics, functional status and disease burden.…”
Section: Introductionmentioning
confidence: 78%
“…10 Moreover, the preventable inpatient cost (PIC) of high-cost patients amounted to the majority (around 70%) of total preventable spending of overall patients as previous studies reported. 6,[10][11][12] Although high-cost patients only occupy a small proportion of the population, they are highly heterogeneous, which has substantial variations in demographics, functional status and disease burden. 7,13,14 Not all hospitalizations are potentially preventable among high-cost patients.…”
Section: Introductionmentioning
confidence: 78%
“…On this basis, we established hypothesis 1: sociodemographic, socio-environmental, and disease factors would affect healthcare utilization. Previous studies have confirmed that inpatient service utilization is highly correlated with high-cost status (15). Hence, we established hypothesis 2: hospitalizations in the initial year would affect the HCP.…”
Section: Associated Factors Of High-cost Persistencementioning
confidence: 84%
“…Studies on high-cost patients have argued that cost is a reasonable measurement of healthcare utilisation,16 17 because cost has far-reaching impacts on the adequacy and performance of patient services 18. In this study, DRG weights were selected as a measurement for overall resource use, reflecting total healthcare costs for each patient admitted to hospital wards.…”
Section: Methodsmentioning
confidence: 99%